SISTEM INFORMASI PELAYANAN JASA SPARE PART ELEKTRONIK BERBASIS WEB PADA CIPTA TEKNIK - Ripai Veri (2022)
The role of technology and information makes data processing very easy by implementing a computerized information system, especially in the business field, it will be more effective. Cipta Teknik is a business in the field of services, especially in the electronic field such as repair, sales, and purchasing of spare parts that still carry out the service process manually via messages and telephones, for the data management process using an inadequate ledger and not using a computer system as a medium. Device. This research designs and builds a website-based information system to facilitate engineering copyrights in the process of electronic services. The method used by the author is the Waterfall method with identifying problems using the PIECES method, PHP programming language using the Laravel framework, the database used is MySQL and testing with the black box testing method. The results obtained are a website-based electronic spare part service information system so that it can help Cipta Teknik in data management and reporting, features such as login, register, add data, edit data, delete data, checkout, history and upload images.